2019
DOI: 10.2134/agronj2019.03.0197
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Consumption and Productivity of Cotton under Sensor‐based Variable‐rate Nitrogen Fertilization

Abstract: Precision N management based on crop reflectance can be used to reduce over‐ and under‐application of N fertilizer to cotton (Gossypium hirsutum L.). The objective of this study was to evaluate the effects of variable‐rate nitrogen management systems (VNMS) based on optical sensing of crop canopy relative to a farmer's uniform‐rate nitrogen application system (FUNS) on N fertilizer consumption, post‐harvest soil N level, and cotton productivity. Eight field strip‐plot trials were conducted on cotton across Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…PA can also reduce nitrogen use and increase nitrogen use efficiency (NUE) by matching nitrogen inputs with crop requirements. For example, a study conducted by Yu et al (2019) reported that variable-rate nitrogen management systems reduced nitrogen consumption by 10.3%-16.9% and improved NUE by 8.3% to 11.0% compared with farmer's uniform-rate nitrogen application system. In another study conducted in China, precision nitrogen management reduced nitrous oxide emissions by 33% compared to conventional nitrogen management practices (Zhang et al, 2018).…”
Section: Core Ideasmentioning
confidence: 99%
“…PA can also reduce nitrogen use and increase nitrogen use efficiency (NUE) by matching nitrogen inputs with crop requirements. For example, a study conducted by Yu et al (2019) reported that variable-rate nitrogen management systems reduced nitrogen consumption by 10.3%-16.9% and improved NUE by 8.3% to 11.0% compared with farmer's uniform-rate nitrogen application system. In another study conducted in China, precision nitrogen management reduced nitrous oxide emissions by 33% compared to conventional nitrogen management practices (Zhang et al, 2018).…”
Section: Core Ideasmentioning
confidence: 99%
“…It is critical that nutrient availability synchronize with plant growth requirements 82 . Potential solutions to improved synchronization include controlled-release fertilizers 90 , split application 91 , fertigation 92 and precision fertilization 93 . It is also important for growers to determine site-specific nutrient budgets and efficiency targets.…”
Section: Cultivation Improvementsmentioning
confidence: 99%
“…Hence, a close study of soil nitrogen can determine the degree of soil fertility and offer a scientific basis for plant cultivation, which can provide guiding suggestions for precise fertilization. It also facilitates the protection of the environment and prevents overfertilization and contamination of the soil [ 5 , 6 , 7 , 8 , 9 ]. Accordingly, the rapid and accurate acquisition of nitrogen content is of great significance to agricultural production and environmental protection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%